ISOLASI, KARAKTERISASI DAN UJI INFEKSI BAKTERI PROTEOLITIK DARI LUMPUR KAWASAN HUTAN BAKAU - Triyanto Triyanto; Alim Isnansetyo; Irfan D. Prijambada; Jaka Widada; Afi Tarmiawati (Universitas Gadjah Mada, 2009)
This research was aimed to isolate proteolytic bacteria that have high ability to hydrolize protein. The sources of bacterial samples were collected from mangrove sediment in Indramayu and Cilacap Regency. Collwel SWYE Modification Agar medium and Skim Milk Agar Medium, which contain pepton and casein, were used for isolating the bacteria. Forty isolates having proteolitic activity were obtained. Three isolates, i.e. Ps.23.1, Ps.27.3 and Ps.23.2, having the highest activity were selected. The selected isolates were able to grow at pH range of 5 to 8. They were also able to grow at NaCl concentration of 0.5-3.5%. Intramuscular injection test on white shrimp (Lithopenaeus vannamei) shows that Ps.23.1 and Ps.23.2 were not pathogenic to shrimp. On the other hand, Ps.27.3 was indicated to cause disease on shrimp. These results indicated that isolates Ps.23.1 and Ps.23.2 potentially can be used as inoculant for bioremedation of brackish water pond. Isolate Ps.23.1 was characterized to be an aerobic, nonmotile, short rod, gram negative bacteria having catalase and oxidase activities. It produced yellowish, circulair, entire colonies. Isolate Ps.23.2 was characterized to be an aerobic, motile, rod, spore forming, gram positive bacteria having catalase and oxidase activities.